PENGOLAHAN DAN PENERIMAAN PRODUK KEDELAI PADA RUMAHTANGGA DI PERKOTAAN DAN PEDESAAN PULAU JAWA INDONESIA - Rina Yenrina; Yuliana Yuliana; Deddy Muchtadi (Jurnal Gizi dan Pangan, 2006)
The study was aimed to get data on kind of processing and acceptance level of local soybean products in rural and urban areas in Java Island. The study locations were South Jakarta (Province of DKI Jakarta); Serang and Tangerang (Province of Banten); Bekasi, Bogor and Bandung (Province of West Java); Purwokerto, Semarang and Solo (Province of Central Java); Yogyakarta (Province of D.I.Yogyakarta); Malang, Jember and Surabaya (Province of East Java). The study was a part of a grand study on processing, acceptance, and consumption pattern of local soybean products at various socio-economic level of households in Java Island in 2005.  The data were obtained by interviewing and observing 2080 households (consisted of 1280 households in urban and 800 households in rural areas) selected randomly. Soybean products that mostly found in the market and consumed by households of Indonesian people, particularly in Java Island, were tempe, tauco, soy-sauce, tofu, tofu-flower, soy-sprout, and oncom.  The mostly ways to process the soy products were stir-frying, deep-frying, toasting, boiling, and ‘bacem’.  Besides, there were also some soy products that consumed directly at a household level after factorized processing, namely as soy-sauce and soy-milk. The average time used to process the soy-products varied, depended on the way of processing and  number of the product processed.  Stir-frying, especially for tempe, tofu, and tauge, was a frequent way done by poor and rich households, both in urban and rural areas.  The products that mostly processed by frying in rural household was tempe, tofu and soybean, meanwhile in urban areas were only tempe and tofu.  The everage time used by urban households to fry the soy-products was shorter than time used by rural households. It was found that more than 90% of households in rural and urban areas stated “like” and “like very much” tempe, tofu, and soy-sauce.  However, the acceptance level of household on tauco, soy-milk, and soy-flower was still low, namely less than 50%.